2013
DOI: 10.1002/ece3.547
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic patterns among social groups of the endangered Central American spider monkey (Ateles geoffroyi) in a human‐dominated landscape

Abstract: Spider monkeys (Genus: Ateles) are a widespread Neotropical primate with a highly plastic socioecological strategy. However, the Central American species, Ateles geoffroyi, was recently re-listed as endangered due to the accelerated loss of forest across the subcontinent. There is inconsistent evidence that spider monkey populations could persist when actively protected, but their long-term viability in unprotected, human-dominated landscapes is not known. We analyzed noninvasive genetic samples from 185 indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 62 publications
3
15
0
Order By: Relevance
“…MHC loci had significantly lower than expected heterozygosity in wild pandas for many studied populations. Multiple explanations for heterozygote deficiency have been proposed, among which the three most common explanations are the presence of null alleles, discontinuities in gene flow, or inbreeding and population decline (Allendorf and Luikart, 2007;Hagell et al, 2013). In our study, heterozygote deficiency was observed at most localities and all studied MHC loci instead of population or locus specific, which suggests that discontinuities in gene flow among isolated populations may explain the loss of heterozygotes in wild pandas.…”
Section: Parasite Infection In Wild Pandassupporting
confidence: 46%
“…MHC loci had significantly lower than expected heterozygosity in wild pandas for many studied populations. Multiple explanations for heterozygote deficiency have been proposed, among which the three most common explanations are the presence of null alleles, discontinuities in gene flow, or inbreeding and population decline (Allendorf and Luikart, 2007;Hagell et al, 2013). In our study, heterozygote deficiency was observed at most localities and all studied MHC loci instead of population or locus specific, which suggests that discontinuities in gene flow among isolated populations may explain the loss of heterozygotes in wild pandas.…”
Section: Parasite Infection In Wild Pandassupporting
confidence: 46%
“…This approach is particularly favourable for the study of migration patterns in endangered primates living in challenging habitats. For instance, genetic analyses have shown the impacts of habitat fragmentation on dispersal behaviour and population genetic structure in the black-and-white howler (Alouatta caraya; Oklander et al, 2010) and black-handed spider monkey (Adeles geoffroyi; Hagell et al, 2013). The recent development of landscape genetic statistical tools allowed further assessment of the influence of environmental features on genetic patterns in endangered primates (Quéméré et al, 2010;.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common explanations for heterozygote deficit is the presence of null alleles (Hagell et al. ). However, this explanation is unlikely for the Chinese egret because all loci were specially amplified utilizing the highly conservative intron sequences flanking exon 2 (Canal et al.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common explanations for heterozygote deficit is the presence of null alleles (Hagell et al 2013). However, this explanation is unlikely for the Chinese egret because all loci were specially amplified utilizing the highly conservative intron sequences flanking exon 2 (Canal et al 2010;Hagell et al 2013;Wang et al 2013;Lei et al 2015;Zhang et al 2015). Alternatively, these deficits might be explained by inbreeding and some forms of nonrandom mating in this Chinese egret population.…”
Section: Discussionmentioning
confidence: 99%